Safe solar drying - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
David Yisa of Minna, Nigeria, asks 'how to maintain the natural colour of sun dried tomatoes and peppers, and avoid blackening. We heard of sulphiting, but do not know the amounts to be safe to consumers'.Several practitioners on the Internet...